HUBUNGAN KUALITAS TIDUR DENGAN DERAJAT HIPERTENSI DI POSBINDU DESA PANERUSAN WETAN BANJARNEGARA: THE CORRELATION BETWEEN HYPERTENSION DEGREE AND SLEEP QUALITY IN PANERUSAN WETAN VILLAGE INTEGRATED POST BANJARNEGARA - Ardina, Catur Putri; Haniyah, Siti; Kurniawan, Wasis Eko (BIMIKI (Berkala Ilmiah Mahasiswa Ilmu Keperawatan Indonesia), 2023)
Introduction: The incidence of hypertension in Central Java, 8,700,512 persons, or 30.4% of the population, have hypertension by the time they are over 15 years old in 2021. Based on the results of measurements on residents aged 18 years and over according to characteristics in Central Java, the highest was in the female sex (40.17%) compared to the male sex (34.17%). Some of the risk factors that lead to hypertension include genetic factors, gender, age, diet, obesity, and lifestyle such as smoking and consuming alcohol. Sleep quality plays an important role for every individual in maintaining sleep conditions and achieving the right REM and NREM sleep stages. The aim of these findings is to identify the characteristics of respondents, characteristics of the degree of hypertension, sleep quality and analyze the relationship between sleep quality and degree of hypertension. Methods: This research applies quantitative through a non-experimental design, data collected using a cross-sectional approach, the total population is 120 respondents with a sample size of 92 respondents. Result: The results of this study indicate that 70 respondents (76,1%) experienced poor sleep quality. In mild hypertension, there were 43 respondents (46.7%).